Biodiversity Conservation in Relation to Plants Used for Medicines and Other Products in Indonesia - Kuswata Kartawinata (The Ethnobiological Society of Indonesia, 2004)
Biological diversity, or biodiversity, refers to all organisms occurring on Earth. Biodiversity is a manifestation of biochemical diversity and can be viewed at three levels: ecosystem, species and genetic. Indonesia has one of the richest endowments of biodiversity — at all levels – of all countries in the world; it is often referred to as a